REAGENTS, MODIFIERS OF THE COMPLEX BINDINGS FOR THE UNIFIED AGGLUTINANT SANDS - D. M. Kukuj; Ju. I. Lednev; I. B. Odarchenko (Литьë и металлургия, 2004)
There are given the calculations, modifiers of bindings for the unified foundry sands.